High Anti-Leishmania IgG Antibody Levels Are Associated With Severity of Mucosal Leishmaniasis - de Lima, Clara Mônica F.; Magalhães, Andrea S.; Costa, Rúbia; Barreto, Carolina C.; Machado, Paulo R. L.; Carvalho, Edgar M.; Lessa, Marcus M.; Carvalho, Lucas P. (Frontiers in Cellular and Infection Microbiology, 2021)
Background Mucosal leishmaniasis (ML), the most inflammatory form of tegumentary leishmaniasis, is predominantly caused by Leishmania braziliensis. The disease is characterized by the development of lesions, mainly in the nasal mucosa. An exacerbated inflammatory response has been associated with the presence of destructive and disfiguring lesions, with stages of severity ranging from small nodulations to the complete destruction of the nasal pyramid architecture. As Leishmania is an intracellular parasite, most immunological studies have emphasized the cell-mediated immune response, while relatively few studies aimed to investigate the role antibodies in protection against, or the pathology of ML. Methods Patients with a confirmed diagnosis of ML were classified according to clinical staging criteria. Serum levels of Leishmania-specific IgG, IgG1 and IgG2 antibodies were determined by ELISA before and after treatment with antimony or antimony plus pentoxifylline. Results Patients in stages IV and V produced higher concentrations of IgG and IgG1 antibodies when compared to those in stage I and II. Significant reductions were seen in the concentrations of IgG and IgG2 antibodies in most patients who responded well to treatment. Conclusions Our data demonstrate an association between IgG antibody titers and the severity of mucosal disease. The observed reduction in antibody production after successful treatment in most patients preliminarily indicates that these tests can be used to aid in the assessment of therapeutic response.